Inflammatory bowel disease in sub-Saharan Africa: a protocol of a prospective registry with a nested case–control study. Issue 12 (22nd December 2020) - Katsidzira, Leolin; Mudombi, Wisdom F; Makunike-Mutasa, Rudo; Yilmaz, Bahtiyar; Blank, Annika; Rogler, Gerhard; Macpherson, Andrew; Vavricka, Stephan; Gangaidzo, Innocent; Misselwitz, Benjamin
Abstract : Introduction: The epidemiology of inflammatory bowel disease (IBD) in sub-Saharan Africa is poorly documented. We have started a registry to determine the burden, phenotype, risk factors, disease course and outcomes of IBD in Zimbabwe. Methods and analysis: A prospective observational registry with a nested case–control study has been established at a tertiary hospital in Harare, Zimbabwe. The registry is recruiting confirmed IBD cases from the hospital, and other facilities throughout Zimbabwe. Demographic and clinical data are obtained at baseline, 6 months and annually. Two age and sex-matched non-IBD controls per case are recruited—a sibling or second-degree relative, and a randomly selected individual from the same neighbourhood. Cases and controls are interviewed for potential risk factors of IBD, and dietary intake using a food frequency questionnaire. Stool is collected for 16S rRNA-based microbiota profiling, and along with germline DNA from peripheral blood, is being biobanked. The estimated sample size is 86 cases and 172 controls, and the overall registry is anticipated to run for at least 5 years. Descriptive statistics will be used to describe the demographic and phenotypic characteristics of IBD, and incidence and prevalence will be estimated for Harare. Risk factors for IBD will be analysed using conditional logistic regression. For microbial analysis, alpha diversity and beta diversity will be compared between cases and controls, and between IBD phenotypes. Mann-Whitney U tests for alpha diversity and Adonis (Permutational Multivariate Analysis of Variance) for beta diversity will be computed. Ethics and dissemination: Ethical approval has been obtained from the Parirenyatwa Hospital's and University of Zimbabwe's research ethics committee and the Medical Research Council of Zimbabwe. Findings will be discussed with patients, and the Zimbabwean Ministry of Health. Results will be presented at scientific meetings, published in peer reviewed journals, and on social media. Trial registration number: NCT04178408 .